Cerebral CIC-NUTM1 rearrangement sarcoma- case report and review of the literature - Jin, Wei; Dong, Ke; Yang, Fan; Zhang, Jianning; Cheng, Gang (Frontiers in Oncology, 2025)
BackgroundEwing sarcoma and Ewing-like sarcoma are both highly aggressive small round cell sarcomas, while CIC rearranged sarcoma (CRS), the most common specific type of Ewing-like sarcoma, exhibits a more aggressive course than Ewing sarcoma and represents a distinct family of sarcomas. NUT midline carcinoma family member 1 (NUTM1) is a characteristic fusion gene of NUT midline carcinoma. In this paper, the intracranial tumor CIC is mainly fused with NUTM1, which is considered to be a molecular variant of CIC sarcoma.Case presentationWe report a 9 years old female patient diagnosed with CIC rearrangement sarcoma with CIC-NUTM1 gene rearrangement and PMS2 frameshift mutation, WHO grade 4. We treated the patient with surgical resection. Due to the poor postoperative condition of the patient, coupled with the inherently poor prognosis of CIC-NUTM1 sarcoma, the patient ultimately had a short survival time and the treatment outcome was not satisfactory.ConclusionWe experienced a rare case of an intracranial tumor with CIC-NUTM1 fusion and a PMS2 frameshift mutation. Due to the small sample size, rapid progression, and poor prognosis associated with this type of tumor, it is essential to enhance understanding and diagnosis of this type of sarcoma.